SADAR WISATA DENGAN PENGMEBANGAN DAN PENATAAN LINGKUNGAN DESTINASI WISATA PANTAI LUNGKAK DESA KETAPANG RAYA, KECAMATAN KERUAK, KABUPATEN LOMBOK TIMUR - Ariputry, Diti Tri; Lestari, Gusti Ayu Puji; Andini, I Gusti Ayu Devgita (Universitas Mataram, 2023)
Ketapang Raya Village is one of the tourist villages in Keruak District, East Lombok Regency. This village has several tourism potentials offered in the form of beach tourism, mangrove forests, and seafood cultivation. One of the tourism icons owned by Ketapang Raya Village is Lungkak Beach, where visitors can spoil their eyes with the beauty of the sunrise which is no less beautiful than other tourist beaches. The development and arrangement of the tourist destination environment is very important for the sustainability of tourism activities, therefore the need for public awareness of the importance of managing tourist attractions properly. The problem found is the lack of awareness of sustainability, maintenance and preservation of the environment and the preservation of local culture. In addition, the lack of effective promotion and marketing has an impact on the lack of information related to Lungkak Beach that must be known to the wider community. Through the work program of the real work lecture to the community about the socialization of tourism awareness with the development and arrangement of the tourist destination environment can help support the tourism sector in Ketapang Raya Village. The output of this work program is the arrangement of tourist destinations in the form of information boards and appeals, trash bins, and other supporting facilities, as well as the development of transit businesses through the creation of tour packages and fishing packages that can improve the community's economy.